Non-Small Cell Lung Cancer as a Second Primary among Patients with Previous Malignancy: Who Is at Risk? - Wu, Geena X. (Clin Lung Cancer, 2017)
BACKGROUND: Patients with prior malignancies may be at increased risk for non-small cell lung cancer (NSCLC). However, the extent of risk is unknown for many cancer types and it is unclear who may benefit from screening. METHODS: The Surveillance, Epidemiology and End Results dataset from 1992-2012 was used to identify patients with prior malignancies who were diagnosed with NSCLC ≥6 months after their initial cancer. Standardized incidence ratios (SIR) for NSCLC were calculated as a ratio of observed to expected cases adjusted by person-years at risk. Cancers with SIR >1.0 had higher risk for NSCLC than expected. Analyses were stratified by sex, radiation, and histology. RESULTS: Among cancer survivors, 32,058 developed NSCLC. Smoking-related (lung, head and neck, bladder) and hematologic malignancies regardless of prior radiation therapy had the highest SIR for NSCLC (range 1.97-4.88). Prior colorectal and renal cancer survivors also had increased SIR for NSCLC (1.16 and 1.21, respectively). Women with previous pancreatic cancer treated with radiation, breast cancer with or without radiation, and those with thyroid cancer demonstrated higher SIR for lung adenocarcinoma. Men with prior irradiated prostate cancer also had elevated SIR (1.08, CI 1.01-1.15) for lung adenocarcinoma. Patients with melanoma, prostate or uterine cancer had lower SIR for NSCLC than expected. CONCLUSIONS: Smoking-related malignancies had the highest risk for NSCLC. Radiation conferred elevated risk for NSCLC for certain cancers. Melanoma, prostate, uterine cancer survivors were at low risk for NSCLC. These results may help identify high-risk screening candidates in the growing population of cancer survivors.